Dixie and free. (22nd June 2022) - Kaldewey, Helma
Abstract : Expanding on findings from my recently published book A People's Music: Jazz in East Germany, 1945–1990 (Cambridge University Press, 2020), in this article I argue that the process of ideologization granted the two most prominent styles of jazz in the GDR, Dixieland and free jazz, overt state support and social acceptance, despite their being on opposite ends of the stylistic spectrum. East German ideologues advanced polarized views on jazz based on their interpretation of the origin of jazz, as well as of their views of the role of jazz in socialism: both Dixieland and free jazz enjoyed legitimized positions in the socialist musical canon based on constructs of 'Volk' (the people) and 'Kommerz' (commercialization). By the late 1970s, both styles of jazz were celebrated at political events and festivals, were utilized as cultural diplomacy, and had become deeply embedded in the socialist musical canon—ultimately contributing to a national East German identity.